Forest Structure, Plant Diversity and Local Endemism in a Highly Varied New Guinea Landscape. (June 2015) - Katovai, Eric; Katovai, Dawnie D.; Edwards, Will; Laurance, William F.
The Island of New Guinea is renowned for its high biodiversity, which arises in part from its complex geology and topographical variability. The island is, however, relatively understudied. We surveyed forest plant communities in the poorly studied Naoro-Brown catchment of the West Koiari region of Papua New Guinea. We identified four forest types—riverine successional forest, lower montane forest, hill forest, and riverine mixed forest—along a 13-km transect, and examined forest structure (tree height, stand density, and biomass) and tree species diversity (species richness, Shannon-Wiener diversity index, and composition) in these forest types. We also assessed the effect of local topography on floristic patterns. Forest structure and species diversity varied greatly among the forest types, with topography strongly affecting species assemblages. These results suggest that highly varied landscapes may contain high beta diversity via intense segregation and establishment of varied vegetation communities. Beta diversity in New Guinea may be higher than expected as such highly varied landscapes are common, yet poorly studied. To effectively conserve biodiversity in New Guinea's forests, protection must include forested landscapes that best represent the topographical variability throughout the island to account for locally endemic species restricted to specific ecological niches.